Triple bottom line in Green Supply Chain Management: a chemical industry study - Cardoso Abdala, Etienne; J. de Oliveira, Eder; Oranges Cezarino, Luciana (Brazilian Journal of Operations & Production Management, 2018)
The management of the green supply chain aims to add practices to preserve the environment in the integrated network of supplies, in order to minimize the use of natural resources and to increase the use of the reuse of materials. The purpose of this article is to identify sustainable practices used by chemical industries of the Triple Bottom Line. Semi-structured interviews were carried out with mangers of medium and small business enterprises. Results show that sustainability is present in both; however, not fully completely obeying the sustainability tripod concept. The medium-sized company has a higher development of its environmental practices and could be considered as a focal company between the supply chain and their suppliers. Small businesses have to develop strategies, especially in terms of providing legal compliance to maintain their partnership with suppliers. None of them performed literature practices of a Green Supply Chain, but the first company, medium sized is ahead in terms of sustainable practices.